Effect of squash (Cucurbita maxima var Suprema) substitution on the quality of the Kutsinta. - Marvida, Charmaine Ortiz (2017.)
Kutsinta is an indigenous snack food which is properly consumed in the Philippines. Because rice flour is its basic ingredients, there is a need to improve its nutritional content primarily the vitamins. This study focused on the utilization of squash (Cucurbita maxima var Suprema) in the production of kutsinta. Three formulations (F1, F2 and F3) with varying squash concentration were subjected to sensory evaluation and physicochemical analysis. Results of the descriptive test by Kruskal-Wallis test at 5% level of significance showed that significant differences were observed in the sweetness, color, fibrousness, squash flavor and firmness among the three formulations except for the squash aroma. Formulation 2 (F2) which contain 64.7% steamed mashed squash was chosen as the most preferred squash kutsinta (MPSK) by Kramers rank sum test at 5% level of significance. Formulation 2 contained 7.26±0.784IU vitamin A content, 50.12±0.41% moisture (wet basis), 0.85±0.21 crude ash (wet basis) and 3.75±0.13% crude fiber (dry basis). Result of independent sample t-test at 95% confidence interval showed that the MPSK contained a significantly higher moisture content (wet basis) and crude fiber (dry basis) than the control but lower contents of crude ash (wet basis). On the other hand, one way ANOVA at 5% level of significance showed that the raw squash had a significantly higher vitamin A content compared to the MPSK and control (P-value=1.338E-10). Comparison of means by Tukey test at 5% levelof significance showed significant differences in the Vitamin A content of raw squash and MPSK; MPSK and control; and raw squash and control. The results show that squash substitution in the preparation of kutsinta could be a feasible product based on its general acceptability as like very much by children within the age group of 5-10 and 11-16 years old, however, result of vitamin A analysis showed that its vitamin A content was not enough to supply the daily recommended intake for children.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Kutsinta; Squash; Cucurbita maxima var Suprema